The Fertility Transition in Sub-Saharan Africa: The Role of Structural Change - Nicolas Büttner; Michael Grimm; Isabel Günther; Kenneth Harttgen; Stephan Klasen (Institute of Labor Economics (IZA), 2023)
Despite the recent economic growth in many countries on the African continent, the region has seen a slow fertility transition. In this study, we explore whether the lack of structural economic change can explain this slow fertility transition. We create a unique panel data set combining Demographic and Health Surveys, Household Income Surveys, and nighttime light intensity data, as an indicator for industrialization, from 57 countries at the sub-national regional level over three decades to analyze the driving forces of fertility transitions across low- and middle-income countries. Our results confirm that household wealth, reduced child mortality, and female basic education are crucial for fertility reductions. Yet, our analysis also highlights the important role of increased female labor force participation in the formal sector, industrialization, increased female secondary education, and the expansion of health insurance coverage. Urbanization appears to have a limited, if any, effect. Our simulations indicate that if high-fertility countries in sub-Saharan Africa had experienced similar structural economic change as low- and middle-income countries with low fertility, their fertility levels could be up to 50% lower.
Keywords: D13; J11; J13; J22; O12; 330; demographic transition; fertility; structural change; human capital; sub-Saharan Africa